Managing Animal Sounds - Some Challenges and Research Directions - Cugler, Daniel Cintra; Medeiros, Claudia Bauzer; Toledo, Luís Felipe (Anais do Brazilian e-Science Workshop (BreSci); 2011: Anais do V e-Science Workshop, 2011)
For decades, biologists around the world have recorded animal sounds. As the number of records grows, so does the difficulty to manage them, presenting challenges to save, retrieve, share and manage the sounds. This paper presents our preliminary results concerning management of large volumes of animal sound data. The paper also provides an overview from our prototype, an online environment focused on management of this data. This paper also discusses our case study, concerning more than 1 terabyte of animal recordings from Fonoteca Neotropical ”Jacques Vielliard”, at UNICAMP, Brazil.